2008
DOI: 10.1088/0268-1242/23/11/114017
|View full text |Cite
|
Sign up to set email alerts
|

Spin orientation of holes in quantum wells

Abstract: This article reviews the spin orientation of spin-3/2 holes in quantum wells. We discuss the Zeeman and Rashba spin splitting in hole systems that are qualitatively different from their counterparts in electron systems. We show how a systematic understanding of the unusual spin-dependent phenomena in hole systems can be gained using a multipole expansion of the spin density matrix. As an example we discuss spin precession in hole systems that can give rise to an alternating spin polarization. Finally we discus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 75 publications
(209 reference statements)
4
99
0
Order By: Relevance
“…4,6,7,27,32,[36][37][38][39][40][41] However, we demonstrate that the validity of the SW-transformed model is limited to a relatively narrow range of parameters, indicating that in general the HH spin splitting contains higher-order terms in the wave vector, which are frequently sizeable. The limited applicability of the simple dispersion relation to realistic heterostructures is relevant to the current understanding of the spin-Hall conductivity, 32,37,39,52 hole spin helix, 40 and Zitterbewegung, 38,41 all of which have been derived based on the assumption that the HH spin splitting is proportional to k 3 .…”
Section: 26mentioning
confidence: 78%
“…4,6,7,27,32,[36][37][38][39][40][41] However, we demonstrate that the validity of the SW-transformed model is limited to a relatively narrow range of parameters, indicating that in general the HH spin splitting contains higher-order terms in the wave vector, which are frequently sizeable. The limited applicability of the simple dispersion relation to realistic heterostructures is relevant to the current understanding of the spin-Hall conductivity, 32,37,39,52 hole spin helix, 40 and Zitterbewegung, 38,41 all of which have been derived based on the assumption that the HH spin splitting is proportional to k 3 .…”
Section: 26mentioning
confidence: 78%
“…Recently, a higher-order contribution of the Rashba SOI, the so-called k 3 (k-cubic) Rashba SOI, has received more attention [14,15]. The Hamiltonian for the k-cubic Rashba SOI is expressed as…”
mentioning
confidence: 99%
“…of the (311) hole g-tensor: Uniquely to (311) oriented GaAs 2D systems, theory [22] and experiment [23] have shown that when a field is applied along the in-plane [233] direction, in addition to an in-plane polarisation with g-factor g xx , there exists an anomalous out-of-plane polarisation due to an off-diagonal term g xz in the gtensor. The Hamiltonian describing the Zeeman term for 2D heavy holes in (311) GaAs is then: …”
mentioning
confidence: 99%